Ultrasound pretreated freeze-drying of carrot: effect on nutritional value, bioactive compounds and microstructure - Md. Hasan Tarek Mondal; Raju Ahmmed; Md. Junaeid Khan (Applied Food Research)
Effect of ultrasound frequency (20, 30 and 40 kHz) and time (3, 5, and 7 min) were applied prior freeze drying to evaluate quality (physical properties, nutritional value, bioactive compounds, antioxidant activity and microstructure) of dried carrot. Quality of freeze dried carrot was also compared to sun dried and hot air dried carrot. Bioactive compound, antioxidant activity and microstructural characteristic were explored through spectrophotometric and SEM analysis. Physical properties improved due to ultrasound pretreatment. Fat (1.45 %) and protein (8.5 %) content was higher only for freeze dried product and mineral content was higher for 30 kHz and five minutes. Beta carotene was higher (988.9 mg/100 g) for 30 kHz and three minutes while sun dried and hot air dried product yielded lower value (933.6 mg/100 g) and (951.4 mg/100 g), respectively. Total phenol (3.74 mg/100 g), flavonoid (9.45 mg/100 g) and antioxidant activity yielded higher value for 30 kHz and five minutes of ultrasound processing. Porous structure was observed for ultrasound processed carrot. The results indicate that quality of the dehydrated carrot could be improved by ultrasound treatment.